Back Cover Image, Volume 3, Number 4, August 2021. Issue 4 (31st August 2021) - Zhu, Ziyi; Zhong, Wentao; Zhang, Yanjia; Dong, Peng; Sun, Shigang; Zhang, Yingjie; Li, Xue
Abstract : Back cover image : Hard carbon is expected to become an anode electrode material for commercial applications of sodium‐/potassium‐ion batteries. However, its structure is more complicated, and the description of energy storage behavior is quite controversial. In article number 10.1002/cey2.111, Xue Li et al. studied the electrochemical performance of biomass‐derived hard carbon materials as the negative electrode of sodium/potassium ion batteries by using magnolia Lima leaf as a precursor, and corresponding sodium/potassium storage mechanism study provides new ideas for the design of high‐performance electrode materials.